THE EFFECTS OF AMINOETHOXYVINYLGLYCINE AND METHYL JASMONATE ON BIOACTIVE COMPOUNDS AND FRUIT QUALITY OF ‘NORTH WONDER’ SWEET CHERRY - Kucuker, Emine; Ozturk, Burhan (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: AVG is an organic ethylene inhibitor. AVG treatments retarded the ripening process, increased fruit sizes and delayed loss postharvest fruit flesh firmness by inhibiting ethylene. MeJA is a natural plant growth regulator and plays a regulatory role in various reactions. Apart from its role in fruit ripening, cell activities like anthocyanin and carotenoid synthesis and inhibitive role in aromatic formation, chlorophyll and lycopene production. Materials and Methods: The present study was conducted to determine the effects of pre-harvest aminoethoxyvinylglycine (AVG) and jasmonate (MeJA) treatments on bioactive compounds, mineral nutrients and other fruit quality characteristics of ‘North Wonder’ sweet variety in 2011. sprayed on experimental trees at 125 mg L-1 dose in two different periods i.e. 3 weeks and 2 weeks before anticipated harvest date. MeJA was applied 3 week before the anticipated harvest date at a dose of 2240 mg L-1 .Results: MeJA significantly increased fruit weight and geometric mean diameter. AVG significantly decreased fruit weight and flesh/stone significantly increased L*, chroma and hue angle values. Effects of both AVG and MeJA on flesh firmness were also found to be significant. While soluble solids concentration and pH values significantly decreased with AVG treatment, titrate acidity significantly increased. Both and MeJA treatments significantly decreased total phenolics (TP), total antioxidant capacity (TAC) and total anthocyanin (TA). Effects on such decreases in TAC and TA were more efficient than MeJA. While the effects of both AVG and MeJA on iron content were significant, effects of only MeJA on nitrogen and phosphor contents were found to be significant. Conclusion: Growth regulators significantly decreased bioactive compounds. AVG was more effective in such decreases than MeJA.